Analysing Radiographic Cardiothoracic Indices Across Age Groups in Pugs: A Comparative Study - Barot, Hiren M; Parikh, Pinesh V; Sodagar, Bhairavi N; Patel, Ashish C; Mayani, Ankush J; Asodiya, Forum A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present research work was carried out to standardize normal reference values of various radiographic indices in 13 healthy Pugs and compare for different age effects. The dogs were divided into two age groups (Group P1, > 1 to < 4 years, n=6, and Group P2, > 4 to < 8 years, n=7) to evaluate whether cardiothoracic radiographic indices differ between the two age groups of dogs. Cardiothoracic radiography was taken without any sedation or anaesthesia and all radiographic measurements were done using software MicroDicom DICOM Viewer. Various cardiothoracic radiography indices studied in the Pug dogs did not vary significantly between the age groups. However, mean values of various cardiothoracic radiography indices, viz., Vertebral Heart Score (VHS), Radiographic Left Atrial Dimension (RLAD), Vertebral Left Atrial Size (VLAS), LAwidth, LAtotal, Thoracic Inlet Heart Size (THIS), Manubrium Heart Score (MHS) and Cardiothoracic Ratio (CTR) can be used for diagnosis of left atrial enlargement and cardiomegaly in DCM affected dogs as an adjunct to echocardiography. Based on present findings, we concluded that mean values of various cardiothoracic radiography indices can be used as breed-specific reference values for screening of dogs suspected for cardiac disease.